Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

(a+b+c)^2/(a+b+c)=(cotA/2+cotB/2+cotC/2)/(cotA+cotB+cotC)

(a+b+c)^2/(a+b+c)=(cotA/2+cotB/2+cotC/2)/(cotA+cotB+cotC)

Grade:11

1 Answers

Yatin Modi
13 Points
2 years ago
Proof:- Numerator=  √s(s-a)/√(s-b)(s-c)  + √s(s-b)/√(s-a)(s-c) + √s(s-c)/√(s-a)(s-b)
After taking LCM we get,
s(s-a)+s(s-b)+s(s-c)/√s(s-a)(s-b)(s-c)
= s[3s-(a+b+c)/∆
 We know that a+b+c = 2s, so
s²/∆= numerator= [(a+b+c)/2]²
 And denominator= cotA+ cotB+ cotC
= CosA/sinA + cosB/sinB + cosC/sinC
By cosine formula and sinA=2∆/bc , sinB=2∆/ac, sinC = 2∆/ab, we get
1/4∆ ×[a²+b²+c²] = denominator.
Now, Numerator/ denominator= (a+b+c)²/(4∆×a²+b²+c²)/4∆
= (a+b+c)²/a²+b²+c²
Therefore, hence proved.

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free

10th iCAT Scholarship Test Registration Form